Access of indigenous groups to integral education: a good practice in teacher training in Costa Rica - Vargas Jiménez, Ileana (2021)
The article arises as a result of the project of Education in Values and Human Rights in Teacher Training. Through the project, a teacher training experience was selected which was developed with a Costa Rican indigenous population; the experience is located at the Universidad Nacional and, for the purposes of the present article, it is called good practice in university teaching. Key participants were interviewed about what they consider to be good practice, what is human rights and values education. The results are analyzed from a qualitative perspective, and demonstrated that good practice, is a pertinent and respectful education of indigenous culture. It is concluded that in pedagogical practice, values must be approached in an integral manner.